2018
DOI: 10.3892/ijmm.2018.3685
|View full text |Cite
|
Sign up to set email alerts
|

Engulfment of platelets delays endothelial cell aging via girdin and its phosphorylation

Abstract: Endothelial cells are critical in angiogenesis and maintain the homeostasis of the blood‑brain barrier (BBB). Platelets (PLTs) are essential in vascular biology, including angiogenesis. The present study aimed to investigate the effect of PLTs on the aging of endothelial cells. Human brain microvascular endothelial cells (HBMECs) and human astrocytes were co‑cultured to mimic the BBB. Transmission electron microscopy was used to observe the engulfment of PLTs. Confocal microscopy was used to observe the co‑loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…27,28 Akt signaling pathway has also been shown to be related to phagocytosis. 8 Other previous studies also showed that SIRT1 and Akt were both involved in aging and platelet phagocytosis, 9,15 and our results provide additional evidence showing the critical roles of SIRT1 and Akt in HEMEC aging.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…27,28 Akt signaling pathway has also been shown to be related to phagocytosis. 8 Other previous studies also showed that SIRT1 and Akt were both involved in aging and platelet phagocytosis, 9,15 and our results provide additional evidence showing the critical roles of SIRT1 and Akt in HEMEC aging.…”
Section: Discussionsupporting
confidence: 80%
“…These results are consistent with previous studies showing that platelet phagocytosis by endothelial cells has a variety of cellular functions, such as inhibiting cell aging and apoptosis and accelerating cell viability. 8,9 Likewise, erythrocyte phagocytosis by ECs has been demonstrated to be facilitated by aging and glycation, 26 suggesting the implication of phagocytosis in cell aging. More importantly, we found that SIRT1 was responsible for diminished cell aging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations